Wedding vow : love whisper : a novel - Cadondon, Alfonso (Bloomington, Indiana : iUniverse, 2018)
"It is a magnificent summer day as Albert, a young sailor, and Glenda, his wife-to-be, prepare to marry in front of an audience of family and friends. But when Glenda suddenly collapses and dies before they can say their vows, Albert is left devastated. He has just lost the love of his life. For months, Albert grieves the death of his beloved. While praying and telling Glenda how much he misses her, he hears love whispers and sees other signs from beyond that he hopes is her spirit communicating with him. Often at his side as a kind and compassionate friend is Brenda Crimson, Glenda's maid-of-honor and best friend who is also hearing love whispers from beyond. As Albert and Brenda find comfort in mourning together, they eventually fall in love. But their relationship is not without challenges as distance, work pressures, and a stalker threaten to change everything once again. In this tale of love lost and love gained, a widowed young sailor falls in love with his former bride-to-be's best friend as they search for comfort in each other's arms and the happily-ever-after they both deserve."--Cover.
Keywords: Men-women relationship -- Fiction; Love stories